2019
DOI: 10.5334/kula.49
|View full text |Cite
|
Sign up to set email alerts
|

Towards Open Annotation: Examples and Experiments

Abstract: This article interrogates how digital text annotation tools and projects facilitate online engagement and virtual communities of practice. With the rise of the Web 2.0 movement and the proliferation of digital resources, annotation has evolved from an isolated practice to a collaborative one. This article unpacks the impact of this shift by providing an in-depth discussion of five web-based tools and two social reading projects. This article examines issues of design, usability, and applicability to pedagogica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Studies of SA in K-12 education, for example, have examined how collaborative reading practices can improve learners’ reading comprehension and attitudes (Chen et al , 2014; Chen and Chen, 2014; Zywica and Gomez, 2008), as well as reading performance abilities such as deep reading, high-level analysis, summarizing and evaluation (Yang et al , 2013). Among researchers and educators in professional learning contexts, SA has been found to support communities of practice and promote the coordination of relevant learning activities such as peer review, meaning-making and the development of disciplinary expertise (Kalir, 2019; McCartney et al , 2018; Seatter, 2019). Given this study’s focus on student perceptions of SA for both learning and sense of community in higher education, our literature review considers: first, SA trends and research opportunities in higher education teaching and learning; and second, insights from a small body of literature specifically concerned with student perceptions of SA.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of SA in K-12 education, for example, have examined how collaborative reading practices can improve learners’ reading comprehension and attitudes (Chen et al , 2014; Chen and Chen, 2014; Zywica and Gomez, 2008), as well as reading performance abilities such as deep reading, high-level analysis, summarizing and evaluation (Yang et al , 2013). Among researchers and educators in professional learning contexts, SA has been found to support communities of practice and promote the coordination of relevant learning activities such as peer review, meaning-making and the development of disciplinary expertise (Kalir, 2019; McCartney et al , 2018; Seatter, 2019). Given this study’s focus on student perceptions of SA for both learning and sense of community in higher education, our literature review considers: first, SA trends and research opportunities in higher education teaching and learning; and second, insights from a small body of literature specifically concerned with student perceptions of SA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Today, annotation tools – and associated instructional arrangements and activity structures – help enable a range of learning practices such as reading comprehension, collaboration and peer review (Gao, 2013; Nokelainen et al , 2005; Schacht, 2015; Zywica and Gomez, 2008). While annotation, in some circumstances, may be an individual and idiosyncratic practice (Marshall, 1997), developments in open and collaborative annotation technologies (Kalir, 2019; Seatter, 2019; Staines, 2018) have advanced what scholars broadly refer to as social annotation (SA). According to Novak et al (2012), SA is a genre of learning technology that enables the annotation of digital resources for information sharing, social interaction and knowledge production.…”
Section: Introductionmentioning
confidence: 99%
“…They also have features that allow users to share their annotations for collaborative work. With the rise of the Web 2.0, the proliferation of digital resources and the ubiquity of digital mobile technologies, such as smartphones and tablet devices, annotation has evolved from an isolated practice to a collaborative one (Seatter, 2019). Such digital tools include Annotation Studio, Hypothes.is, and Google Docs, as well as annotation projects such as Open Utopia and Infinite Ulysses.…”
Section: Affordances Of Digital Readingmentioning
confidence: 99%
“…They concluded that students' resistance to reading may be related to a lack of motivation as a result of low reading ability. Other studies have also reported that some tertiary students have difficulties in engaging with reading strategies such as using annotation tools for collaborative and deep reading (Seatter, 2019), making connections from one digital text to another using keyword searches (Park & Kim, 2016), deploying critical reading strategies such as evaluation and analysis (Manarin et al, 2015), and evaluating digital texts for their reliability by comparing and finding contradictions in the texts (Baildon & Baildon, 2012). As such, students, even at the tertiary level, could benefit from reading instruction and not have educators assume that they already have the reading skills, especially for digital reading (Fisher et al, 2011).…”
Section: Affordances Of Digital Readingmentioning
confidence: 99%
“…Alternatively, are there greater learning opportunities (as well as increased risks) in making the annotations fully public? Kennedy (2016) and Seatter (2019) have both provided detailed and balanced reviews from a tertiary teacher's perspective of using Hypothes.is (and in Seatter's case, other annotation tools) in their English literature courses. Both are positive about online annotation activities in general and Hypothes.is in particular, but helpfully draw attention to potential pitfalls and barriers to success, such as the risk of learners annotating different websites containing the same text, or inadvertently posting publicly instead of to a group.…”
Section: Using Hypothesis For Web Annotationmentioning
confidence: 99%